Statistical Methods for the Evaluation of University Systems - Attanasio, Massimo; Capursi, Vincenza; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2011)
This book presents a collection of statistical methods and procedures to assess data coming from educational systems. The topics examined include: statistical methods for constructing composite indicators, applied measurements, assessment of educational systems, measurement of the performance of the students at Italian universities, and statistical modeling for questionnaire data. Other issues are the implications of introducing different assessment criteria and procedures to the Italian university system.
Part I - Introduction: Different Perspectives of the Evaluation of the Italian University System -- Part II - The Evaluation in the Italian Universities. Student Teaching Evaluation -- Part III - The Evaluation in the Italian Universities. Statistical Methods for Careers and Services Evaluation -- Part IV - Research Design and data for Evaluation: University between the High School and the Labour Market.
Keywords: Education; Assessment; Statistics; Social sciences; Education; Assessment, Testing and Evaluation; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Methodology of the Social Sciences; Electronic books